ANALISIS KEMENANGAN PARTAI GOLKAR DI KABUPATEN TANAH DATAR, SUMATERA BARAT SEJAK 1999 DITINJAU DARI PERSPEKTIF TEORI PATRON KLIEN - Irvan Ansyari; Priyatno H; Fitriyah . (Journal of Politic and Government Studies, 2015)
Golkar domination in Tanah Datar regency is an interesting research, at the territory which has a very good of islamic law in its culture, golkar can beat all of islamic party in Tanah Datar. Golkar Party in Tanah datar show us that political grouping cant happen there as we see in the java, that is can wee se on the result of public election of a regent, golkar’s domination at parlemen, and also a massive golkar’s networking until in the village level. On this study, researchers using a qualitative approach that will generate data through observation,in deeph interviews with a elected informantThe research show that the influence of Golkar and its networking in Tanah Datar Regency was until village level. A best figure at all of Tanah Datar regency is a golkar member. This networking is the key of Golkar victory in Tanah Datar Regency. This all figures make a patron klien relationship between a Golkar member and the society. That golkar member reputed can give a social assurance to the society so it make a society sympathy to this party.Keyword : Golkar Party, Patron Client